Accelerating Dissolution of Polyacrylamide in Offshore Oil Field. (8th September 2015) - Yu, Qin; Lu, Xiangguo; Zhang, Defu; Xie, Kun
<x xml:space="preserve">Abstract</x> The solubility of polyacrylamide significantly reduces the efficiency of polymer flooding in offshore oil fields, because of the low performance of polyacrylamide and the special environment. The objective of this paper is to investigate a novel approach to accelerate the dissolution of hydrolyzed polyacrylamide (HPAM) by adding a co‐solvent cholamine (MEA). We investigated the effects of MEA on the microstructure and the performance of HPAM. Results showed that the addition of MEA and the temperature rise greatly shortened the dissolution time of HPAM, while improved the rheological property and seepage behavior. The enhanced solubility of polyacrylamide and the performance of polymer solution can be attributed to the enlarging of the molecular clew size, the stretching of molecular chains and the lowering of the glass transition temperature of HPAM. The new approach has high practical and the economic values for applications of the polymer flooding technology in offshore oilfields with complex reservoir conditions.